UPAYA KELOMPOK KEPENTINGAN KEEP AMERICA SAFE MEMENGARUHI KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERKAIT ISU TERORISME TAHUN 2009-2013 - Wiadnyana, I Wayan Variady; Dharmiasih, D.A. Wiwik; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   The goal of this research is explaining the efforts of Keep America Safe interest group in influencing United States of America’s (US) foreign policy related to terrorism issues in 2009 to 2013. This interest group is chosen as research o bject because. This interst group disagree on the changing of US foreign policy direction on President Barack Obama’s administration. Various attempts have been done by Keep America Safe movement to influence US administrative, namely lobbying congress, raising social awareness through social media and mass media. This interest group used Youtube and Facebook to share information and raising broader supports. This research uses descriptive-qualitative method and using foreign policy decision making and interest group as its conceptual framework. A moment before this interest group dismissed in 2013, Keep America Safe was unable to get US ppublic attention and congress. Hence, US government still changing their foreign policy direction.   Keywords :  Foreign Policy, Interest Group, Keep America safe, President Barrack Obama, United States of America, War on Terrorism Policy